ANALISIS BERITA HOAKS DI ERA POST-TRUTH: SEBUAH REVIEW - Suharyanto, Cosmas Eko (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2019)
Â This study aims to provide an initial analysis of how Indonesia in the post-truth era is becoming a world threat. Modern countries such as America and Britain can be ruined by post-truth storms, this is an alarm for the Indonesian people. The potential threats are of course different and in fact seen from the very diverse social situation of Indonesian people (ethnicity, religion, language, culture) the potential threats will be more dangerous if there is no good mitigation. Study literature the researchers use to provide a baseline analysis that occurs, to further deepen based on the current situation through the exploration of information from credible media. The pattern of hoax news dissemination through social media received by the people of Indonesia and the results of surveys from various survey institutions give a clear picture that Indonesia is also not immune to the post-truth tsunami. The main medium of post-truth is alternative media, and post-truth is constrained if media literacy and fact-checking become a culture of community communication.